2011
DOI: 10.3892/etm.2011.249
|View full text |Cite
|
Sign up to set email alerts
|

Sessile serrated adenoma shares similar genetic and epigenetic features with microsatellite unstable colon cancer in a location-dependent manner

Abstract: Abstract. Genetic and epigenetic features of sessile serrated adenoma (SSA), a precursor lesion to colon cancer with microsatellite instability (MSI), were investigated. The aim of this study was to clarify whether there are location-dependent genetic and epigenetic features in SSA. Twenty-two patients with proximal SSAs and 8 with distal SSAs were recruited. Twenty-two patients with tubular adenoma (TA) and 66 with proximal colon cancer were studied for comparison. Genetic and epigenetic features were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 29 publications
(35 reference statements)
3
22
1
Order By: Relevance
“…This was similar to other reports where a majority of CIMP-H SSAs and HPs were proximally located [19, 27, 33]. We found that CIMP-H was significantly associated with BRAF mutant serrated polyps and a negative association existed between KRAS mutation and CIMP-H which was also observed in studies by O'Brien et al and Yang et al [19, 29].…”
Section: Discussionsupporting
confidence: 92%
“…This was similar to other reports where a majority of CIMP-H SSAs and HPs were proximally located [19, 27, 33]. We found that CIMP-H was significantly associated with BRAF mutant serrated polyps and a negative association existed between KRAS mutation and CIMP-H which was also observed in studies by O'Brien et al and Yang et al [19, 29].…”
Section: Discussionsupporting
confidence: 92%
“…Although we detected high levels of methylation accumulation in SSA/P, our data also suggested that DNA methylation accumulation was not completed by the adenoma stage, and the methylation of genes, including MLH1 , may increase during development from adenoma to cancer in the serrated pathway. Compared with our results, lower frequency of MLH1 methylation in SSA/P have been reported by other groups . This result might be explained, in part, by differences in the tumor size and histological appearance.…”
Section: Discussioncontrasting
confidence: 88%
“…It has been reported that distinct genetic and epigenetic features exist in the proximal SSA/p and the distal SSA/p . 14 Another possibility is that these left-sided polyps are in fact hyperplastic polyps with morphology indiscernible from SSA/p due to various factors (such as orientation, processing artifact etc.). Further study with more definitive standard is needed to clarify this issue, as the current biomarkers such as BRAF mutation is not specific enough to distinguish SSA/p from HP.…”
Section: Discussionmentioning
confidence: 99%